2022
DOI: 10.1200/op.22.00090
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Cancer Genetic Testing and Variants of Uncertain Significance in the Hispanic Population of South Texas

Abstract: PURPOSE: Racial and ethnic disparities have included a lack of access to both genetic testing and research, resulting in poor understanding of the genomic architecture in under-represented populations. The South Texas population is primarily of Hispanic background and has been largely devoid of genetic services. We extended access to this underserved population and uncovered genetic variants previously not observed, emphasizing the need to continually improve both genomic databases and clarification of variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Table 1 summarizes the descriptive characteristics of the included interventions ( n = 16). Most interventions took place within the US ( n = 13), 12 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 and the remaining interventions were conducted in Latin American countries, including Brazil ( n = 2) 72 , 73 and Mexico ( n = 1). 74 Of the 16 interventions included, 14 (87.5%) of the interventions were evidence‐based 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 and 2 (12.5%) interventions were not evidence‐based.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the descriptive characteristics of the included interventions ( n = 16). Most interventions took place within the US ( n = 13), 12 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 and the remaining interventions were conducted in Latin American countries, including Brazil ( n = 2) 72 , 73 and Mexico ( n = 1). 74 Of the 16 interventions included, 14 (87.5%) of the interventions were evidence‐based 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 and 2 (12.5%) interventions were not evidence‐based.…”
Section: Resultsmentioning
confidence: 99%
“…Most interventions took place within the US ( n = 13), 12 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 and the remaining interventions were conducted in Latin American countries, including Brazil ( n = 2) 72 , 73 and Mexico ( n = 1). 74 Of the 16 interventions included, 14 (87.5%) of the interventions were evidence‐based 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 and 2 (12.5%) interventions were not evidence‐based. 61 , 70 The most frequently hereditary cancer syndromes were hereditary breast and ovarian cancer ( n = 14, 77.8%), 12 , 60 , 61 , 63 , 64 , 65 , 66 , 67 , 69 , 70 , 71 , 72 , 73 , 74 Lynch syndrome ( n = 6, 37.5%) 61 , 64 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that the receipt of services through a translator among Spanish-preferring patients results in suboptimal care [ 22 ], including misinterpretation of information and less opportunity for shared decision making [ 23 , 24 ]. Specific areas that are particularly challenging are an explanation of VUS results, which are more common in H/L individuals undergoing genetic testing [ 25 ]. Data from our current study demonstrate enhanced understanding of content related to different types of test results.…”
Section: Discussionmentioning
confidence: 99%
“…The issue expands knowledge on focused topics such as disparities in cardio-oncology care as reviewed by Suero-Abreu et al 8 with potential solutions to improve care. Differences in genetic variants in the Hispanic/Latinx patient population were observed through the genetic counseling efforts of Soewito et al 9 In their editorial, Raez et al 10 outlined some of the ongoing challenges in genetic testing and treatment outcomes in patients with lung cancer. In addition, the importance of cancer care communication was a welcomed addition to the series by Ochoa et al, 11 with their focus on the young adult childhood cancer survivors, their parents, and health care teams.…”
mentioning
confidence: 99%